Análise aeroacústica de um duto de ar condicionado através da dinâmica de fluidos computacional - Meira, Lucas de Souza (2020)
The present research deals with the aeroacoustic problem in a complex flow inside an HVAC (Heating and Ventilation Air-Conditioning) system. This work aims to investigate the flow-induced noise generation in a turbulent pipe flow by means of Computational Fluid Dynamics (CFD). A simplified HVAC geometry was adopted as a benchmark case. This geometry represents the main noise sources: pressure driven flow and flow around an obstacle. In order to develop the present analysis and to find the most accurate approach for this application, we evaluated different advective discretization schemes in the context of DES (Detached Eddy Simulation). Comparisons are established with experimental data of benchmark cases, for which gauge pressure in specific regions, sound pressure level and velocity fields are evaluated. Simulations are carried out using an in-house code, i.e. UNSCYFL3D, which was developed at the Federal University of Uberlândia. By means of this work, we were able to find the most accurate setup parameters for such a problem. Reynolds Averaged Navier-Stokes turbulence models did not yield satisfactory results, whereas the Detached Eddy Simulation (DES) was found to produce much more accurate results, obviously at a higher computational cost. It is concluded that DES, along with the central difference scheme for the advection, is a viable approach for computational aeroacoustics of HVAC ducts.